KRITIK SOSIAL DAN KEMANUSIAAN DALAM LIRIK LAGU KARYA IWAN FALS - Susanti, Winda; Nurmayani, Eva (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2020)
This research aimed to describe humanity and social critics in the lyrics of Iwan Fals?s songs. The research used descriptive qualitative where the data in form of words. The techniques of collecting data were library study.  Furthermore, the techniques of analyzing the data were: identification, selection, data reduction, analyzing, interpretation, performing the data, and conclusion. The result of analyzing and discussion related to social critics dealing with government and human and pain. Based on analyzing result it can be: social critic in government aspect was about the government was still not good, and pain, someone felt pain because of  government on sociopolitical.Keywords: social critic, humanity, songs? lyrics.